PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK PADA GURU ‎DI SMPIT MUTIARA INSANI DELANGGU KLATEN - Romdhoni, Muhammad; Mujiburrohman, M; Abdullah, Mu’in (Al’ulum Jurnal Pendidikan Islam, 2024)
The purpose of this study is to find out the role of the school principal in improving teacher pedagogic competence at SMPIT Mutiara Insani Delanggu, then knowing that teacher pedagogic competence is applied, then knowing the obstacles of the school principal in increasing teacher pedagogic competence. This research method is a qualitative research method, research techniques are carried out through observation, interviews and documentation. The subjects used in this study were the principal and 3 teachers. The steps in analyzing the data are by triangulating with the theory that is already understood. The results of research at SMPIT Mutiara Insani Delanggu are. The results of the research at SMPIT Mutiara Insani Delanggu are: first, the role of the principal in improving the pedagogical competence of teachers at SMPIT Mutiara Insani Delanggu is very good, because it is found that the principal has a role in developing the pedagogical competence of teachers in this school and the principal always provides guidance related to this competence, namely through teacher work meetings which are held once a week then adding material by holding workshops and webinars. Second, the role of the principal in applying pedagogical competence to teachers is that every morning the principal checks the presence of teachers to be at school then the principal provides scheduled and unscheduled supervision activities. Third, the inhibiting factors in applying the pedagogical competence of teachers are facilities and infrastructure that are less accommodating or supportive, there are some teachers who do not understand pedagogical competence and teachers must first learn how to apply the right methods to be delivered to students.endala of this pedagogical competence is, the weakness of teachers in mastering this material is caused by the existence of facilities and infrastructure that have not accommodated.